Environmental assessment of a landfill leachate treatment plant: Impacts and research for more sustainable chemical alternatives. (10th May 2018) - Postacchini, Leonardo; Ciarapica, Filippo E.; Bevilacqua, Maurizio
Abstract: The aim of this study is to evaluate, from an environmental point of view, the performance of various technologies applied to the treatment of municipal landfill leachate. The study has been led in an Italian wastewater treatment plant and it applies the principles of the Life Cycle Assessment (LCA) technique, using ReCiPe as the assessment method. This study shows how the operating stage of a wastewater treatment plant, that applies chemical and physical treatments, can affect the following four environmental impact categories: "Freshwater Eutrophication", "Freshwater Ecotoxicity", "Marine Ecotoxicity" and "Human Toxicity". Within this operating stage, the study shows the relevant environmental impacts generated by the use of polyaluminum chloride (PAC) as a coagulant chemical agent and sodium hydroxide (caustic soda) as a pH control chemical agent. In order to investigate these results, and to discover more eco-friendly alternatives, two LCA comparisons have been carried out, comparing respectively the above two agents to analogous and common substitutes: ferric chloride as a coagulant agent and calcium hydroxide (lime) as a pH control agent. These comparisons demonstrate the higher environmental impacts of the use of ferric chloride over PAC and of sodium hydroxide over calcium hydroxide. Ferric chloride has shown to have more than double the environmental impact of PAC in 9 environmental categories out of the 10 considered, while calcium hydroxide has been able to cut down the negative environmental impacts of the sodium hydroxide of more than 65% in all the environmental categories. Considering the highly positive environmental results achieved from our study, whenever possible, a substitution of calcium hydroxide to sodium hydroxide and of PAC to ferric chloride is strongly recommended. Graphical abstract: Image 1 Highlights: Life Cycle Assessment of a municipal landfill leachate treatment plant. Main responsible inputs for the environmental impacts: PAC, NaOH and electricity. LCA comparisons: PAC vs FeCl3 and NaOH vs Ca(OH)2 . Ca(OH)2 proven better than NaOH for more than 65% in all environmental categories. PAC proven better than FeCl3 for more than 50% in 9 environmental categories.